2011
DOI: 10.1007/s12393-011-9033-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Nonthermal Methods for Food Allergen Control

Abstract: The incidence of food allergy has been increasing over the years, leading to a demand for methods aimed to reduce allergens from food products. The study of food processing on allergen reactivity has largely focused on thermal treatments; however, novel food processing techniques, such as a variety of nonthermal methods, are being explored to potentially create hypoallergenic products. Nonthermal methods are oftentimes advantageous, as they have the ability to retain organoleptic properties, such as nutrient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 119 publications
(163 reference statements)
0
78
0
Order By: Relevance
“…This presumption was 17 further supported by the research findings showing a reduction in O2 barrier property in polymer by Ar-induced cross-linking (Houston et al, 2002). Other researchers suggest that cold plasma treatment may alter the solubility, but not the diffusivity, of water molecules, so that the bulk property of water vapor permeability may remain unchanged (Shriver and Yang, 2011;Oh et al, 2016). Pankaj et al (2014) found that the intensity of the amide II band increased after DBD plasma treatment due to the occurrence of a shift from a β-sheet structure to an α-helical configuration and the formation of more extensive hydrogen bonding between the proteins, leading to a reduction in the non-bonded peptide groups in the zein films (Pankaj et al, 2014c).…”
Section: Physical and Mechanical Properties Of Protein Based Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…This presumption was 17 further supported by the research findings showing a reduction in O2 barrier property in polymer by Ar-induced cross-linking (Houston et al, 2002). Other researchers suggest that cold plasma treatment may alter the solubility, but not the diffusivity, of water molecules, so that the bulk property of water vapor permeability may remain unchanged (Shriver and Yang, 2011;Oh et al, 2016). Pankaj et al (2014) found that the intensity of the amide II band increased after DBD plasma treatment due to the occurrence of a shift from a β-sheet structure to an α-helical configuration and the formation of more extensive hydrogen bonding between the proteins, leading to a reduction in the non-bonded peptide groups in the zein films (Pankaj et al, 2014c).…”
Section: Physical and Mechanical Properties Of Protein Based Filmsmentioning
confidence: 99%
“…They are capable of binding to the allergens at a specific site (epitope), resulting 23 in various immunologic reactions. Changes in protein configuration can make changes in epitopes to the extent that they can no longer be identified by IgE antibodies or give any clue to immune response (Shriver and Yang, 2011).…”
Section: Food Allergenicitymentioning
confidence: 99%
“…The PUV radiation contains approximately 54% UV-C, 25% visible light, and 20% infrared light (OmsOliu et al, 2010;Shriver et al, 2011). The PUV light can be thousands of times more intense than conventional, continuous mercury UV light (Dunn et al 1995;Krishnamurthy et al, 2009).…”
Section: Nonthermal Methods 621 Pulsed Ultraviolet Lightmentioning
confidence: 99%
“…The continuous system can also be used for batch treatment by setting the conveyor speed to zero. The PUV treatment is a process of photophysical, photothermal and photochemical effects (Chung et al, 2008;Krishnamurthy et al, 2009;Yang et al, 2010;Shriver and Yang, 2011). Normally, PUV is regarded as nonthermal as long as the duration of exposure is short (e.g., seconds), as the temperature rise is insignificant; however, a prolonged PUV exposure (e.g., minutes) can incur significant temperature rise and moisture loss of the sample, where both the nonthermal (mostly due to the UV spectrum) and photothermal (mostly from the infrared spectrum) effects co-exist ).…”
Section: Nonthermal Methods 621 Pulsed Ultraviolet Lightmentioning
confidence: 99%
“…Although thermal treatments can be used on many products to alter food allergen reactivity, thermal processing has also been known to modify organoleptic properties, including flavor, color, and nutrient content (Holdsworth, 1985). Therefore, novel non-thermal food processing techniques are being explored in order to create hypoallergenic products (Shriver & Yang, 2011). Variable success of methods for allergenicity reduction, due to limited knowledge of allergen and epitope structures and the factors governing their stability, imposes need for an empirical approach (Soler-Rivas & Wichers, 2001).…”
Section: Introductionmentioning
confidence: 99%